Paying Taxes 2012 : The Global Picture - World Bank; International Finance Corporation; PricewaterhouseCoopers (World Bank, Washington, DC, 2017)
The objectives of the study are to provide data which can be compared between economies on a like-for-like basis; to facilitate the benchmarking of tax systems within relevant economic and geographical groupings, which can provide an opportunity to learn from peer group economies; and to enable an in-depth analysis of the results which can be used to help identify good practices and possible reforms. The private sector plays an essential role in contributing to economic growth and prosperity. Companies contribute to socio-economic development by employing workers, improving the skills and knowledge base, buying from local suppliers and providing products and services that improve people's lives. They also contribute to government revenues through generating and paying taxes. The paying taxes study is unique because it generates a set of indicators that measure the world's tax systems from the point of view of business and also because it covers the full range of taxes paid in 183 economies, measuring how business complies with the different tax laws and regulations in each economy.